Analysis and Application of the Certainty Factor Method in the Diagnostic Expert System for Broiler Chicken Diseases - Ragil Ardiansyah; Yuhandri; Silfia Andini (Journal of Computer Scine and Information Technology, 2023)
An expert system is a system that uses human knowledge recorded in a computer to solve problems that normally require human expertise. Certainty Factor is a clinical parameter value given by MYCIN to indicate the level of trust. The certainty factor is also a way of combining belief and disbelief in a single number. Certainty factor introduces the concepts of belief/belief and disbelief/unbelief. In the system analysis stage, the author analyzes to find weaknesses in the system that is currently running in an organization or company with the aim that the system can be proposed for improvement. Implementing the program that has been designed requires a tool in the form of a computer or laptop, which requires three supporting components to operate the computer or laptop itself, such as hardware, software, and brainware. The expert system application has been running with the Certainty Factor method and to make a diagnosis on chickens the user can choose a value according to the Certainty Factor Interpretation that has been given and processed with the CF expert. Based on the tests carried out, the value of system accuracy with experts is almost the same . And the Inference engine works well, according to the pre-programmed rules. After diagnosing a chicken disease, the system will display how to treat and handle sick broiler chickens